2019
DOI: 10.3390/ijms20112742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spaceflight and Simulated Microgravity on YAP1 Expression in Cardiovascular Progenitors: Implications for Cell-Based Repair

Abstract: Spaceflight alters many processes of the human body including cardiac function and cardiac progenitor cell behavior. The mechanism behind these changes remains largely unknown; however, simulated microgravity devices are making it easier for researchers to study the effects of microgravity. To study the changes that take place in cardiac progenitor cells in microgravity environments, adult cardiac progenitor cells were cultured aboard the International Space Station (ISS) as well as on a clinostat and examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…However, most cardiovascular microgravity physiology studies have been conducted either in non-human models or at tissue, organ, or systemic levels. While recent studies of human cardiac progenitor cells have demonstrated that microgravity can enhance their differentiation and maintenance (Baio et al., 2018, Camberos et al., 2019, Jha et al., 2016), none have addressed the effects of spaceflight on differentiated cardiomyocytes. Using 6-well plates optimized for microgravity, we sent live hiPSC-CMs from three individuals to the ISS as an in vitro human model for microgravity exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, most cardiovascular microgravity physiology studies have been conducted either in non-human models or at tissue, organ, or systemic levels. While recent studies of human cardiac progenitor cells have demonstrated that microgravity can enhance their differentiation and maintenance (Baio et al., 2018, Camberos et al., 2019, Jha et al., 2016), none have addressed the effects of spaceflight on differentiated cardiomyocytes. Using 6-well plates optimized for microgravity, we sent live hiPSC-CMs from three individuals to the ISS as an in vitro human model for microgravity exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Space research and investigations on cell signaling processes in the growth and development of cells exposed to microgravity (µg) is currently a hot topic in cancer research and regenerative medicine [1][2][3][4][5]. Prostate cancer is the fifth leading cause of cancer mortality in men, with the second highest cancer incidence worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of μ G on mammalian cells have been studied extensively on the International Space Station (ISS), or by using clinostats for ground-based experiments. It is well known that μ G affects various cellular functions such as altered cell adherence, protein expression, gene expression, morphology, increased apoptosis and decreased proliferation rates [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%